Influence of hexagonal boron nitride nanosheets on phase transformation, microstructure evolution and mechanical properties of Si3N4 ceramics. Issue 10 (August 2021) - Tatarková, Monika; Tatarko, Peter; Kovalčíková, Alexandra; Dlouhý, Ivo; Dusza, Ján; Šajgalík, Pavol
Abstract: Fully dense Si3 N4 materials with 1 wt.% (∼ 1.5 vol.%) and 2 wt.% (∼ 3.0 vol.%) h-BN nanosheets were prepared by spark plasma sintering at 1750 °C with the dwell of 7 min under a pressure of 50 MPa in a vacuum. BN nanosheets with different dimensions were prepared by ultrasound-assisted liquid phase exfoliation of h-BN powder, followed by centrifugation at different speeds (1000 rpm and 3000 rpm). The addition of BN nanosheets hindered the particle rearrangement stage of sintering, which resulted in the delayed α→β phase transformation of Si3 N4 . To study a direct effect of BN nanosheets on the mechanical properties of Si3 N4, the results were compared to the monolithic Si3 N4 with similar grain size and α/β-Si3 N4 ratio. The addition of 2 wt.% h-BN nanosheets (1000 rpm) increased both the fracture toughness (∼ 26 %) and the strength (∼ 45 %) of Si3 N4, when compared to the monolithic Si3 N4 with similar microstructure.